Bacterial Modulation of Plant Ethylene Levels - Gamalero, Elisa; Glick, Bernard R. (Plant physiology (Bethesda), 2015)
A focus on the mechanisms by which ACC deaminase-containing bacteria facilitate plant growth.Bacteria that produce the enzyme 1-aminocyclopropane-1-carboxylate (ACC) deaminase, when present either on the surface of plant roots (rhizospheric) or within plant tissues (endophytic), play an active role in modulating ethylene levels in plants. This enzyme activity facilitates plant growth especially in the presence of various environmental stresses. Thus, plant growth-promoting bacteria that express ACC deaminase activity protect plants from growth inhibition by flooding and anoxia, drought, high salt, the presence of fungal and bacterial pathogens, nematodes, and the presence of metals and organic contaminants. Bacteria that express ACC deaminase activity also decrease the rate of flower wilting, promote the rooting of cuttings, and facilitate the nodulation of legumes. Here, the mechanisms behind bacterial ACC deaminase facilitation of plant growth and development are discussed, and numerous examples of the use of bacteria with this activity are summarized.